2021
DOI: 10.1038/s41467-021-22511-7
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical excitability modulation guides human perception under uncertainty

Abstract: Knowledge about the relevance of environmental features can guide stimulus processing. However, it remains unclear how processing is adjusted when feature relevance is uncertain. We hypothesized that (a) heightened uncertainty would shift cortical networks from a rhythmic, selective processing-oriented state toward an asynchronous (“excited”) state that boosts sensitivity to all stimulus features, and that (b) the thalamus provides a subcortical nexus for such uncertainty-related shifts. Here, we had young adu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 120 publications
9
71
0
Order By: Relevance
“…Interestingly, some of the EEG spectral modulations associated to drowsiness (steeper 1/f slope and reduced IAF) were also identified when comparing meditation and rest conditions in experienced meditation practitioners (see Figure 3G). In this way, both a relative decrease in IAF and a steeper 1/f slope have been previously associated to reduced arousal levels (Cantero et al, 2002;Kosciessa et al, 2021;Lendner et al, 2020;Mierau et al, 2017). Since a relative decrease in arousal can be expected during both drowsiness and a state of relaxation during meditation practice (Jagannathan et al, 2018;Matko et al, 2021;Petitmengin et al, 2017), we speculate that steeper 1/f slope and reduced IAF during meditation in experienced practitioners are reflective of reduced arousal due to relaxation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Interestingly, some of the EEG spectral modulations associated to drowsiness (steeper 1/f slope and reduced IAF) were also identified when comparing meditation and rest conditions in experienced meditation practitioners (see Figure 3G). In this way, both a relative decrease in IAF and a steeper 1/f slope have been previously associated to reduced arousal levels (Cantero et al, 2002;Kosciessa et al, 2021;Lendner et al, 2020;Mierau et al, 2017). Since a relative decrease in arousal can be expected during both drowsiness and a state of relaxation during meditation practice (Jagannathan et al, 2018;Matko et al, 2021;Petitmengin et al, 2017), we speculate that steeper 1/f slope and reduced IAF during meditation in experienced practitioners are reflective of reduced arousal due to relaxation.…”
Section: Discussionsupporting
confidence: 55%
“…Recent evidence has shown that the commonly termed '1/f trend' varies within subjects and is functionally relevant (Donoghue, Haller, et al, 2020;Kosciessa et al, 2021;Lendner et al, 2020;Voytek et al, 2015;Waschke et al, 2021). For example, the slope of the 1/f trend is thought to be reflective of excitation-inhibition balance in the brain (steeper slope is associated to greater inhibition) (R. Gao et al, 2017), thereby having important implications for cognition and consciousness (Kosciessa et al, 2021;Lendner et al, 2020;Ouyang et al, 2020). Crucially, it has been recently shown that changes in the 1/f trend of the EEG spectrum can conflate the estimation oscillatory activity (Donoghue, Dominguez, et al, 2020;Donoghue, Haller, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Task performance may become more variable as people try new strategies to learn more about the context and seek out further information that could be used to make inferences (Hsu et al, 2005;Yu & Dayan, 2005; see also, Kosciessa et al, 2021).…”
Section: Uncertainty At the General Cognitive Levelmentioning
confidence: 99%
“…This network interacts with broader networks involved in cognitive control, including the frontal-parietal network and the cingulo-opercular Downloaded from http://direct.mit.edu/nol/article-pdf/doi/10.1162/nol_a_00044/1927613/nol_a_00044.pdf by guest on 13 July 2021 network (including anterior cingulate cortex, supplementary motor area, and insula; T. Wu et al, 2020). Recent evidence suggests that the thalamaus may play a central role in cortical shifts that occur during decision making under uncertainty (Kosciessa et al, 2021). To give one example, when comparing situations with unexpected uncertainties, where there is risk that is unknown beforehand (e.g., a deck of cards where probabilities are unknown; also called ambiguous choices), to those with expected uncertainties, where risk is known beforehand (e.g., a familiar deck of cards where probabilities are known; also called risky choices), there is differential activation of frontal (orbitofrontal cortex) vs. striatal (basal ganglia, caudate) areas.…”
Section: Uncertainty At the General Cognitive Levelmentioning
confidence: 99%